Variability in Suicidal Ideation is Associated with Affective Instability in Suicide Attempters with Borderline Personality Disorder - Rizk, Mina M. (Psychiatry, 2019)
OBJECTIVE: Suicidal ideation (SI) is heterogeneous with different patterns and risk factors. SI can be persistent with stable severity but may also fluctuate rapidly over a short period of time. The latter pattern is likely associated with affective instability and may consist of activation of SI at times of stress, that then subside. Although affective instability is a hallmark of borderline personality disorder (BPD), little is known about SI variability in BPD. We hypothesized that SI variability would be associated with affective instability in BPD suicide attempters. METHOD: Sample included 38 females with BPD and history of suicidal behavior. SI was assessed over one week using ecological momentary assessment (EMA) at 6 epochs daily. The relationship between SI variability (i.e., change of SI from one epoch to another) and SI severity (i.e., average scores across epochs), and affective instability, assessed using the Affective Lability Scale (ALS), were examined. Possible confounding effects of depression severity and impulsiveness were tested. RESULTS: Participants demonstrated high ALS scores and wide range of SI variability. ALS scores predicted SI variability, even after controlling for depression severity. Although ALS also predicted SI severity, this association was driven by depression severity. ALS did not correlate with impulsiveness score. CONCLUSIONS: Affective instability may predict SI variability in BPD suicide attempters independent of depression severity. This supports our model of suicidal subgroups with different constellations of clinical aspects and risk factors. Future studies could examine these associations in larger samples and different populations to determine implications for suicide prevention.